2014
DOI: 10.1111/apa.12817
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine therapy is associated with impaired cerebral autoregulation in preterm infants

Abstract: Dopamine therapy was associated with decreased CA in preterm infants. We were unable to determine whether dopamine directly impaired CA or was merely an indicator of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 29 publications
(32 reference statements)
4
37
1
Order By: Relevance
“…In this study, however, infants with an HSDA received inotropes more often than controls. Dopamine administration has previously been associated with impaired cerebrovascular autoregulation in preterm infants [16] and a mismatch between cerebral perfusion and oxygenation in newborn piglets [17]. We speculate that the higher rate of administration of dopamine might have contributed to their findings of decreased cerebral rSO 2 in the presence of an HSDA, in contrast to all previous reports.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, however, infants with an HSDA received inotropes more often than controls. Dopamine administration has previously been associated with impaired cerebrovascular autoregulation in preterm infants [16] and a mismatch between cerebral perfusion and oxygenation in newborn piglets [17]. We speculate that the higher rate of administration of dopamine might have contributed to their findings of decreased cerebral rSO 2 in the presence of an HSDA, in contrast to all previous reports.…”
Section: Discussioncontrasting
confidence: 58%
“…Its use, however, is concerning, as it has been shown to have variable effects on outcome and possibly leads to neurodevelopmental delays [1,18,29,33]. Dopamine therapy, in particular the first-line agent used in the study center, has been shown to lead to decreased end-organ perfusion, failure to restore cerebral autoregulation, and failure to increase cerebral perfusion in the setting of increased BP [19,26,34,35,36]. In adult and pediatric data, dopamine use as compared to norepinephrine or epinephrine therapy leads to higher mortality rates [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive hypotension therapy may lead to worse outcomes (mortality and IVH) than allowing permissive hypotension in patients with no signs of systemic hypoperfusion [24,25]. Vasopressor therapy is also controversial as some studies indicate that it is independently associated with impaired cerebral autoregulation and brain injury [4,26,27]. This underlines the need to adequately define the BP threshold that will lead to cerebral injury in order to target therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that treated hypotension was associated with short-and long-time morbidity, which suggests an indirect relationship between inotropes and a pressure-passive cerebral circulation (22,23). Furthermore, a direct negative influence of dopamine on CAR has been reported (24). Conversely, several studies demonstrated a protective role of inotropes by means of increasing CBF (25)(26)(27).…”
Section: Car In Preterm Infants With Necmentioning
confidence: 99%